Cutaneous anthrax associated with handling carcasses of animals that died suddenly of unknown cause: Arua District, Uganda, January 2015-August 2017. - Freda Loy Aceng; Alex Riolexus Ario; Phoebe Hilda Alitubeera; Mukasa Matinda Neckyon; Daniel Kadobera; Musa Sekamatte; Denis Okethwangu; Lilian Bulage; Julie R Harris; Willy Nguma; Deo Birungi Ndumu; Joshua Buule; et al. (Public Library of Science (PLoS), 2021)
Background Anthrax is a zoonotic disease that can be transmitted to humans from infected animals. During May-June 2017, three persons with probable cutaneous anthrax were reported in Arua District, Uganda; one died. All had recently handled carcasses of livestock that died suddenly and a skin lesion from a deceased person tested positive by PCR for Bacillus anthracis. During July, a bull in the same community died suddenly and the blood sample tested positive by PCR for Bacillus anthracis. The aim of this investigation was to establish the scope of the problem, identify exposures associated with illness, and recommend evidence-based control measures. Methods A probable case was defined as acute onset of a papulo-vesicular skin lesion subsequently forming an eschar in a resident of Arua District during January 2015-August 2017. A confirmed case was a probable case with a skin sample testing positive by polymerase chain reaction (PCR) for B. anthracis. Cases were identified by medical record review and active community search. In a case-control study, exposures between case-patients and frequency- and village-matched asymptomatic controls were compared. Key animal health staff were interviewed to learn about livestock deaths. Results There were 68 case-patients (67 probable, 1 confirmed), and 2 deaths identified. Cases occurred throughout the three-year period, peaking during dry seasons. All cases occurred following sudden livestock deaths in the villages. Case-patients came from two neighboring sub-counties: Rigbo (attack rate (AR) = 21.9/10,000 population) and Rhino Camp (AR = 1.9/10,000). Males (AR = 24.9/10,000) were more affected than females (AR = 0.7/10,000). Persons aged 30-39 years (AR = 40.1/10,000 population) were most affected. Among all cases and 136 controls, skinning (ORM-H = 5.0, 95%CI: 2.3-11), butchering (ORM-H = 22, 95%CI: 5.5-89), and carrying the carcass of livestock that died suddenly (ORM-H = 6.9, 95%CI: 3.0-16) were associated with illness. Conclusions Exposure to carcasses of animals that died suddenly was a likely risk factor for cutaneous anthrax in Arua District during 2015-2017. The recommendations are investigation of anthrax burden in livestock, prevention of animal infections through vaccinations, safe disposal of the carcasses, public education on risk factors for infection and prompt treatment of illness following exposure to animals that died suddenly.